2013
DOI: 10.1007/s11892-013-0431-7
|View full text |Cite
|
Sign up to set email alerts
|

What the Genetics of Lipodystrophy Can Teach Us About Insulin Resistance and Diabetes

Abstract: Genetic lipodystrophic syndromes are rare diseases characterized by generalized or partial fat atrophy (lipoatrophy) associated with severe metabolic complications such as insulin resistance (IR), diabetes, dyslipidemia, nonalcoholic fatty liver disease, and ovarian hyperandrogenism. During the last 15 years, mutations in several genes have been shown to be responsible for monogenic forms of lipodystrophic syndromes, of autosomal dominant or recessive transmission. Although the molecular basis of lipodystrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 95 publications
1
23
0
1
Order By: Relevance
“…Both HIV and hepatitis C (HCV) infections have been associated with a higher risk of diabetes mellitus (DM), but results are conflicting . In HIV‐infected patients, insulin resistance (IR) and DM have been related to lipodystrophy and exposure to the first generation of protease inhibitors (PI) or to D‐thymidine nucleoside analogues and didanosine . In HCV‐infected patients, apart from cirrhosis from any cause, which is a well established risk factor for IR and DM, it has been suggested that HCV infection could directly induce IR and DM by interfering with glucose metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Both HIV and hepatitis C (HCV) infections have been associated with a higher risk of diabetes mellitus (DM), but results are conflicting . In HIV‐infected patients, insulin resistance (IR) and DM have been related to lipodystrophy and exposure to the first generation of protease inhibitors (PI) or to D‐thymidine nucleoside analogues and didanosine . In HCV‐infected patients, apart from cirrhosis from any cause, which is a well established risk factor for IR and DM, it has been suggested that HCV infection could directly induce IR and DM by interfering with glucose metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…Lipoatrophy may vary from being partial, co-existing with adipose tissue depots in ectopic sites, to generalized [1]. These syndromes are usually linked with severe metabolic complications, such as insulin resistance, diabetes mellitus, dyslipidemia, hepatic steatosis, and hypertension [2, 3]. Loss of adipose tissue seems to give rise to both lipodystrophy and metabolic disorders [2], which suggests that it is the absence of fat tissue and the consequent leptin deficiency that leads to insulin resistance [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…These syndromes are usually linked with severe metabolic complications, such as insulin resistance, diabetes mellitus, dyslipidemia, hepatic steatosis, and hypertension [2, 3]. Loss of adipose tissue seems to give rise to both lipodystrophy and metabolic disorders [2], which suggests that it is the absence of fat tissue and the consequent leptin deficiency that leads to insulin resistance [4, 5]. Furthermore, adipocytes provide a benign location to accumulate lipids and, thus, when they are absent, lipids will store in the liver, muscle, and ectopic tissues, causing significant metabolic complications [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with diabetes, attributable to familial partial lipodystrophy linked to LMNA (nine women), PPARG (one man) or PLIN1 mutations (one woman), or to congenital generalized lipodystrophy attributable to AGPAT2 mutations (four women, one man), were included in the study (Table S1). The patients presented with different forms of lipodystrophic syndromes, with insulin resistance and dyslipidaemia attributable to previously described causative mutations . Their age and BMI were 39.2 ± 4.0 years and 23.9 ± 0.7 kg/m 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%